Pertimbangan Hakim Dalam Menjatuhkan Vonis Terhadap Lansia Demensia Yang Melakukan Perbuatan Tindak Pidana - Tia, Hendry Fand; Helvis, Helvis; Khantika, I Made; Nardiman, Nardiman (Multidisciplinary Journal of Education , Economic and Culture, 2024)
Child molestation is a despicable act that is not only committed by any adults, but also elderly people who may suffer from dementia that may be at cronic stage. Criminal liability for elderly people with dementia has to be medically observed or medical forensic observation by certified mental health doctors. If a psychiatric expert states that the defendant suffer from a severe mental health that may be exampted by the law, then the defendant has the potential to be waved from penal punishment. The aim of this research is to determine the judge's considerations in giving sentences to defendants who is an elderly with cronic dementia. This research uses a normative juridical research method. The results of his research showed that elderly people with dementia were still found guilty because they were proven to have committed a criminal act, in their consideration the judge took into account aggravating and mitigating factors so that in their decision the judge sentenced the defendant to serve his sentence not in prison but sent him to a mental hospital. to be treated. In conclusion, the judge still sentenced the defendant because the judge believed that the defendant committed his actions before experiencing dementia, so the Panel of Judges at the South Jakarta District Court sentenced the defendant to 6 (six) months in prison and a fine of Rp. 20,000,000.00 (twenty million rupiah), and pay restitution in the amount of Rp. 38,736,550 (thirty-eight million seven hundred thirty-six thousand five hundred and fifty rupiah).